Audit adjustments and the discontinuity in earnings distribution around zero - Lim, Chu Yeong (2023)
Purpose: Previous research in auditing has used the probability of small profits or losses as a measure of audit quality. The purpose of this paper is to investigate the validity of the underlying assumption in prior audit literature that auditing mitigates clients’ inclination towards loss avoidance and to shed light on the debate regarding earnings discontinuity. Design/methodology/approach: This paper compares the discontinuity in earnings distribution around zero, both before and after auditing. Findings: Using a unique data set that contains both recorded and waived adjustments, the authors find that audit adjustments do not reduce the discontinuity in earnings distribution around zero. Research limitations/implications: The results advise caution in using the probability of small profits or losses as a measure of audit quality. The findings suggest the discontinuity in earnings around zero may not be caused by loss avoidance achieved through accounting misreporting, which falls under the purview of auditing. Originality/value: This research makes unique contributions beyond those of prior studies. By incorporating waived adjustments, the authors are able to conduct more comprehensive tests and explore richer details of audit adjustments that were not available in previous studies. The proportion of losses in this study's sample aligns with that in prior US research, which enhances the generalisability of the authors’ findings and minimizes the influence of inherent discrepancies in auditors' motivations to curb loss avoidance.